ANALISIS KEANDALAN SISTEM KESELAMATAN BANGUNAN SEBAGAI PROTEKSI KEBAKARAN PADA GEDUNG POLDA JAWA TENGAH - Gultom, Theresia Hardianti; Kurniawan, Bina; Lestantyo, Daru (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
The building located in Regional Police of Central Java is included in a state building that should meet the requirement of Occupational Safety and Health (K3) and have rescue facility from the disaster or emergency situation based on the required National Standard of Indonesia (SNI). The fire in Regional Police building of Central Java in 2015 was caused by electricity installation, so the new Regional Police building was built. However, there is no research and study about the fire standard after it was built. The research was aimed at analyzing the reliability level of building safety system in Regional Police building in Central Java as the fire protection system. The type of the research was observational descriptive study in which the actual situation is described and interpreted without the treatment or intervention on the research variable. The subjects of this research were the staffs of office service bureau (yanma) as well as facility and infrastructure bureau (sarpras) of Regional Police in Central Java. The data were collected using observation sheet with the standard guideline of Pd-T-11-2005-C concerning the safety checking of the fire in the building by Public Works Department of Republic Indonesia and the interview guideline of building reliability component. The result of this research shows that the score of safety reliability in Regional Police building in Central Java is 85,19% and is included in good category. Nevertheless, the improvement is required in the sub-component of active protection system which is included in poor category.